The urban-rural dichotomy in the Indonesian documentaries; "Nona nyonya?" and "Untuk apa?" - Saraswati, Asri (Wacana, Journal of the Humanities of Indonesia, 2012)
The media play a pivotal role in the democratization process in Indonesia and this is among others apparent in the surge of films, both fiction and documentaries that have been produced after the end Suharto's decades of control over the media. It is important to note, however, that compared with fiction films, the documentary genre remains rather unpopular in Indonesia. Indonesian documentary films struggle to depict stories of the subaltern and those living in the "periphery" in order for them to be seen and heard by the greater masses and by those in power - the ones in the "centre" or Jakarta. This paper discusses the connection between urban and rural voices and its impact in the documentary films Nona nyonya? (Miss mrs?, 2008) and Untuk apa? (What's the point?, 2008) produced by Kalyana Shira Films, an organization well-known for its work on gender issues using film as medium. Departing from the notion that the film industry itself is still largely Jakarta-centred, this article focuses on the way urban settings and voices are used to create rhetoric, and the impact of the domination of these urban voices over the rural ones.